Synthesis and characterization of Fe (iron), Co (cobalt), Ni (nickel) containing metal organic frameworks (MOFs) - Galın, Çağla. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2022., 2022)
In recent years, scientists and industries have been interested in metal organic frameworks (MOFs), a class of porous materials. Metal organic frameworks are formed by connecting metal clusters or ions with organic linkers. In addition to porous structures of MOFs, they have high surface areas, structural diversity, adjustable chemical functionality, high thermal stability, and easy synthesis. MOF can be used in many applications such as gas storage (e.g., hydrogen, methane, acetylene, and carbon dioxide), catalysts, and energy applications (e.g., batteries and supercapacitors). In this study, cheaper starting materials (metal salts of iron (Fe), cobalt (Co), and nickel (Ni)) based MOFs were synthesized via sonochemical synthesis method due to its fast, energy -efficient, and environment friendly method, and fumaric acid and terephthalic acid were used as organic linkers. The effects of temperature, pH, concentration, and solvent on MOF material were investigated. X-Ray Diffraction Analysis (XRD), Scanning Electron Microscope/Energy Dispersive X-Ray Analysis (SEM /EDX), and Infrared (IR) Spectroscopy, were used for characterization of synthesized compounds. In this thesis, the synthesis conditions for Fe (iron) with fumaric acid-based MOFs are optimized for the first time by using 1 mmol starting materials at 75 ⁰C and pH=natural (2.57) in 90 minutes sonication. Fe, Co, and Ni containing MOFs are synthesized for the first time by using terephthalic acid as organic linker and DMF as solvent, successfully by exploiting 90 minutes sonication. When pH of organic ligands solutions increased for faster deprotonation of organic ligands, iron oxide nanoparticles, cobalt (II) hydroxide and nickel (II) hydroxide were obtained instead of MOF structures.
Keywords: Metal-organic frameworks.; Organometallic chemistry.